Effectiveness evaluation of whole-body electromyostimulation as a postexercise recovery method - de la Camara Serrano, M. A.; Pardos, A. I.; Veiga, O. L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Whole-body electromyostimulation (WB-EMS) devices are now being used in health and sports training, although there are few studies investigating their benefits. The objective of this research was to evaluate the effectiveness of WB-EMS as a postexercise recovery method and compare it with other methods like active and passive recovery. METHODS: The study included nine trained men (age =21±1 years, height =1.77±0.4 m, mass =62±7 kg). Three trials were performed in three different sessions, 1 week apart. Each trial, the participants completed the same exercise protocol and a different recovery method each time. A repeated measures design was used to check the basal reestablishing on several physiological variables (lactate, heart rate, percentage of tissue hemoglobin saturation, temperature, and neuromuscular fatigue) and to evaluate the quality of recovery. The non-parametric Wilcoxon and Friedman ANOVA tests were used to examine the differences between recovery methods. RESULTS: The results showed no differences between methods in the physiological and psychological variables analyzed. Although, the blood lactate concentration showed borderline statistical significance between methods (P=0.050). Likewise, WB-EMS failed to recover baseline blood lactate concentration (P=0.021) and percentage of tissue hemoglobin saturation (P=0.023), in contrast to the other two methods. CONCLUSIONS: These findings suggest that WB-EMS is not a good recovery method because the power of reestablishing of several physiological and psychological parameters is not superior to other recovery methods like active and passive recovery.